2017
DOI: 10.3389/fnagi.2017.00038
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Shape Changes, Hippocampal Atrophy and Cortical Thinning in Future Alzheimer's Disease Patients

Abstract: Efficacy of future treatments depends on biomarkers identifying patients with mild cognitive impairment at highest risk for transitioning to Alzheimer's disease. Here, we applied recently developed analysis techniques to investigate cross-sectional differences in subcortical shape and volume alterations in patients with stable mild cognitive impairment (MCI) (n = 23, age range 59–82, 47.8% female), future converters at baseline (n = 10, age range 66–84, 90% female) and at time of conversion (age range 68–87) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 101 publications
(170 reference statements)
5
33
0
Order By: Relevance
“…This concurs with the occurrence of significant amounts of Aβ in the thalamus of AD (Braak & Braak, ). Shape abnormalities in the thalamus associated with Aβ have also been reported in cognitively normal individuals (Schroeder et al, ) as well as in MCI patients who showed cognitive worsening over a 2‐year period (Kalin et al, ). Interestingly, we also found that some of the surface change in the thalamus were also due to changes in shape only (i.e., surface remains abnormal even when analyses were corrected for size and global scalings), particularly in regions which did not show surface changes when investigating the effect of local volume change.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This concurs with the occurrence of significant amounts of Aβ in the thalamus of AD (Braak & Braak, ). Shape abnormalities in the thalamus associated with Aβ have also been reported in cognitively normal individuals (Schroeder et al, ) as well as in MCI patients who showed cognitive worsening over a 2‐year period (Kalin et al, ). Interestingly, we also found that some of the surface change in the thalamus were also due to changes in shape only (i.e., surface remains abnormal even when analyses were corrected for size and global scalings), particularly in regions which did not show surface changes when investigating the effect of local volume change.…”
Section: Discussionmentioning
confidence: 83%
“…A vertex‐based surface approach was used to investigate Aβ‐associated local surface changes in subcortical structures and whether these changes related more to local volume or shape. Surface‐based approaches have proven efficient in the detection of subtle surface abnormalities in subcortical structures in AD, MCI, and cognitively normal individuals (Csernansky et al, ; de Flores et al, ; Kalin et al, ; Leh et al, ; Schroeder et al, ). Unlike our previous analyses using subcortical overall volumes, we found that subcortical regional PiB retention values were associated with the surface of the bilateral hippocampus and thalamus and the right pallidum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We next examined how aging affects TRiC and sHSPs levels in the brain. Proteostat staining of aged brain sections compared to young counterparts indicated that the increase in Proteostat + inclusions was not restricted to aged NSPCs (Figures 1D-G, S1C), but was widespread in other regions; particularly the cortex and striatum (Figures 7A, B; S7A), areas typically affected in age-related proteopathies (Kalin et al, 2017; Rub et al, 2016). We observed a decline in TRiC protein levels in Sox2 + cells of the aged SGZ stem cell niche compared to those of young adult mice; both in vivo in mouse brain sections (Figures 7C, S7B) and in vitro in isolated NSPCs (Figures 7D).…”
Section: Resultsmentioning
confidence: 95%